The effects of APOE on brain activity do not simply reflect the risk of Alzheimer's disease. - Trachtenberg, A; Filippini, N; Cheeseman, J; Duff, E; Neville, M; Ebmeier, K; Karpe, F; Mackay, C (2012)
Possession of the APOE-ε4 allele is the best established genetic risk factor for sporadic Alzheimer's disease (AD), while the ε2 allele may confer protection against the disease. Previous functional magnetic resonance imaging (fMRI) studies have shown an effect of APOE genotype on brain function, typically by comparing only ε4 carriers with noncarriers. Here we included a wide range of genotype groups to determine how closely the effects of APOE on brain function are related to differences in relative risk for AD. We used functional magnetic resonance imaging (fMRI) to compare the pattern of activation during an episodic encoding task and during a counting Stroop task in 76 adults, aged 32 to 55, with different APOE genotypes (23 ε2/ε3, 20 ε3/ε3, 26 ε3/ε4, and 7 ε4/ε4). Strikingly, participants with an increased risk (ε4 carriers) and with a decreased risk (ε2 carriers) for AD both showed increased activation, relative to ε3 homozygotes, during both tasks. The increased activation was due to decreased deactivation or paradoxical activation of nontask-related regions of the brain, which suggests an intrinsic effect of APOE on the differentiation of functional cortical networks. These results question the often assumed link between APOE, the blood oxygenation level dependent (BOLD) response, and AD risk.